Review of the genera Pristocera Klug and Pristepyris Kieffer (Hymenoptera: Bethylidae, Pristocerinae) of Russia and adjacent territories - Fadeev, Kirill I. (Zootaxa, 2021)
The genera Pristocera Klug and Pristepyris Kieffer from Russia and neighboring countries are reviewed for the first time. Pristocera is represented in Russia by two species. Pristocera depressa (Fabricius) is first recorded from a number of regions in southwestern European Russia (Krasnodar and Stavropol Territories, Kabardino-Balkaria, Chechnya, Ingushetia, and North Ossetia Republics), as well as for Azerbaijan, Armenia, and Turkey. The illustrated redescriptions of both sexes of the type species of Pristocera depressa is provided, and the lectotype of Bethylus depressus from J.C. Fabricius collection is designated. A new species, Pristocera morawitzi sp. nov. is described and illustrated based on males and females from south of Russia, Azerbaijan, and Armenia. Pristepyris is represented in Russia by single species, Pristepyris masii (Giordani Soika). It is also indicated for the first time from Rostov and Volgograd Provinces and Stavropol Territory of Russia, Azerbaijan, and Georgia. A previously unknown female of P. masii is described and illustrated. The original key to both sexes of all studied genera and species is provided.